On the Re-practice of the Artistic Style of "Zaifen Series" Huangmei Opera—From the Newly-composed Huangmei Opera "Liu Chi Alley - Width" - Gao, Rongbo (Journal of Social Science and Humanities, 2024)
"Liu Chi Alley - Width" is another newly-composed Huangmei Opera produced by Anqing Zaifen Huangmei Opera Troupe. This opera presents multifaceted character portrayals, drawing materials and inspiration from both history and reality, and collaborating with cross-disciplinary arts in terms of expression techniques. It inherits the characteristics of the "Zaifen Huangmei" series in artistic style. Taking this opera as an entry point, one can glimpse some of the artistic style features of the newly-composed Huangmei Operas in the "Zaifen Series".